STUDI TENTANG BUSANA TRADISIONAL PASUMANDAN PADANG - Ramadani, Emilia April; Ernawati, Ernawati; Adriani, Adriani (Journal of Home Economics and Tourism, 2015)
Traditional Clothing Pasumandan is one of the traditional dress at the wedding ceremony. This study aimed to describe Traditional Clothing Design Pasumandan Padang that in terms of models, materials, colors, embellishments and philosophical meaning contained in Traditional Clothing Pasumandan Padang. This research uses qualitative descriptive method. Collecting data in this study is by observation, interview and documentation. analysis techniques used are data reduction, data presentation and conclusion. To get the data by performing an extension observation, triangulation of data and auditing. Traditional Clothing Pasumandan research results Padang consists of kuruang bajaik basiba, made of red velvet, ornate gold thread and stab pinhead, philosophy contained in the model symbolizes covered genitalia, decorative motifs used kaluak paku symbolizing the close kinship , daunbodi symbolizes a woman there must be stored, which symbolizes broad-mindedness siba Minang people. Holsters / songket using cotton, macau and gold thread, red hearts, meaning the philosophy contained is the value manners that are owned by women Minang, salendang bajaik made of red satin, wearing ornate gold thread embroidery and puncture pinhead, salendang bajaik symbolizes child support, that the Minang women are responsible for their offspring. Suntiang ketek pan made of golden yellow, motif used motifs of flora and fauna, edit symbolizes kinship values upheld by the Minang community. Jewelry is a necklace worn girder pnyiaram armpit / girder ula, made of a material pan golden yellow and silver, where the necklace symbolizes that women are always in a circle of truth, has a solid foundation, bracelets symbolize sustenance that obtained more than desired. Tarompa Tatutuik red, wearing ornate velvet embroidered with gold thread and stab pinhead. Meaning contained in sandals, that person should have the properties Minang closed and not easily open, also a customary courtesy.Keywords : baju kuruang bajaik basiba, kaluak paku ,daunbodi,Sarung/songket ,salendang bajaik ,Suntiang ketek ,kalung pnyiaram galang ketek/galang ula,Tarompa tatutuik